Aplicación de la herramienta de análisis de dientes de sierra en intercambios de WhatsApp - Lumbreras Mayans, Julia (Verba hispanica, 2025)
Digital discourse analysis has undergone significant expansion in the last decade within in-context language studies. This paper aims to contribute to the growing body of research examining communication in digital environments by focusing on the structures of colloquial conversation. The study has two main objectives: first, to demonstrate that the sawteeth tool (Espinosa, 2016) can be applied to conversational exchanges produced on WhatsApp; and second, to determine whether turn-taking in digital discourse displays a level of complexity equal to or even greater than that found in co-present oral communication. For this analysis, a corpus was compiled consisting of the interactions of six participants on the instant messaging platform WhatsApp. The methodology follows Val.Es.Co.’s proposal for discourse segmentation (2014).
Keywords: alternancia de turnos; análisis del discurso digital; analiza spletnega diskurza; awteeth, turn-taking; colloquial Spanish; dientes de sierra; digital discourse analysis; espanol coloquial; govorne izmenjave; orodje nazobčanega vzorca; pogovorna španščina; WhatsApp